Investigation of the Impact of Polycystic Ovaries on Maternal Risks of Reproductive-Age Females - sampana fatima (Journal of Rawalpindi Medical College, 2025)
The objective of this study was to investigate the association between polycystic ovaries (PCOs) and maternal complications during pregnancy. Methodology: This prospective case-control study was conducted at Shahida Islam Medical Complex from November 2024 to June 2025. Data was collected from inpatient pregnant females. Demographic information was recorded; patients were divided into cases and controls depending upon the status of PCOs as diagnosed clinically by Rotterdam criteria. Before delivery, 5ml of venous blood was collected for estimation of lab parameters. Patients were followed till delivery, and maternofetal outcomes were recorded. Results: A significant association between PCOS and gestational diabetes was found (ꭕ=11.35, p< 0.0001). Logistic regression analysis, using a backward stepwise method, identified LH, FSH, Testosterone, Insulin Resistance, and Systolic BP as significant predictors of Gestational Diabetes. Notably, higher levels of LH and FSH were associated with increased risk (p < 0.0001 and p = 0.0000, respectively). The correlation matrix confirmed strong correlations between Testosterone and LH (r = 0.83), and between Insulin Resistance and Glucose levels (r = 0.83), highlighting metabolic dysfunctions in PCOS. Conclusion: These findings underscore the critical role of hormonal imbalances and insulin resistance in increasing the risk of pregnancy complications in PCOS patients, emphasizing the need for early screening and intervention.